The Interactive Role of Green Knowledge Acquisition In The Relationship Between Green Learning And Environmental Resilience: An Applied Study of The Opinions of A Sample of Employees At Al-Kafeel Meat Production Company - Ameera Ajel (Penerbit Jurnal Indonesia, 2026)
The current research aims to identify the interactive role of acquiring green knowledge in the relationship between green learning with its dimensions (cognitive, skill-based, organisational, technological) and sustainable resilience with its dimensions (economic sustainability, social sustainability, environmental sustainability). It is an applied study based on the opinions of a sample of 132 employees from Al-Kafeel Meat Production Company. The research problem was represented by the main question: